2015
DOI: 10.1016/j.addbeh.2014.10.040
|View full text |Cite
|
Sign up to set email alerts
|

Parent, peer, and executive function relationships to early adolescent e-cigarette use: A substance use pathway?

Abstract: Introduction Little is known about influences on e-cigarette use among early adolescents. This study examined influences that have been previously found to be associated with gateway drug use in adolescents: demographic (age, gender, ethnicity, free lunch), social contextual influences of parents and peers, and executive function deficits (EF). Methods A cross-sectional survey was administered to 410 7th grade students from two diverse school districts in Southern California (M age=12.4 years, 48.3% female, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 109 publications
(77 citation statements)
references
References 41 publications
(63 reference statements)
2
68
2
Order By: Relevance
“…Our estimates are close to those from a study conducted in Hawaii in 2013 that reported 29% of high school students having ever tried an e-cigarette (Wills et al, 2015), which appears to be the highest reported to date. Our middle school (7 th grade) estimates of lifetime use (13.4%) are also substantially higher than the national estimate of 3.9% (Arrazola et al, 2015), and slightly higher than estimates from a southern California study of 7 th graders in two school districts that found 11% of students had ever tried e-cigarettes (Pentz et al, 2015). The higher rates of e-cigarette use reported here compared with studies from other states and national studies may be due to geographic/ regional differences in e-cigarette use or may be due to regional differences in retail environments, policy environment, or sample composition (Orange County has more nonWhite students than other regional studies).…”
Section: Discussioncontrasting
confidence: 79%
“…Our estimates are close to those from a study conducted in Hawaii in 2013 that reported 29% of high school students having ever tried an e-cigarette (Wills et al, 2015), which appears to be the highest reported to date. Our middle school (7 th grade) estimates of lifetime use (13.4%) are also substantially higher than the national estimate of 3.9% (Arrazola et al, 2015), and slightly higher than estimates from a southern California study of 7 th graders in two school districts that found 11% of students had ever tried e-cigarettes (Pentz et al, 2015). The higher rates of e-cigarette use reported here compared with studies from other states and national studies may be due to geographic/ regional differences in e-cigarette use or may be due to regional differences in retail environments, policy environment, or sample composition (Orange County has more nonWhite students than other regional studies).…”
Section: Discussioncontrasting
confidence: 79%
“…16 Research is needed to determine whether use of e-cigarettes by nonsmoking adolescents could function as a gateway to combustible cigarette use, leading to increases in cigarette use, either by renormalizing smoking and the social acceptability of smoking or by reducing the perceived risks associated with initiation of use as a result of exposure to marketing of e-cigarettes as a cessation aid. 12,17 Tobacco control measures in California have been successful in reducing cigarette use by adolescents; in our study, cigarette use among southern California adolescents was low. The success of the California availability of tobacco, including youth access.…”
Section: Discussionmentioning
confidence: 56%
“…E-cigarette use is much more frequent among adult smokers compared with non-smokers 1 ; therefore, this finding could reflect exposure to e-cigarettes in the proximate social environment, which has been associated with adolescent e-cigarette use 18 . Nonetheless, whether there is an independent association between caregiver or peer smoking and the likelihood of trying e-cigarettes remains an open question 19 . We also conducted analyses focused on the subset of children considered at high-risk of smoking due to their antisocial behaviours or lack of parental support following on from research that has attempted to disentangle these effects 14 .…”
Section: Discussionmentioning
confidence: 99%